2021
DOI: 10.28940/terra.v39i0.992
|View full text |Cite
|
Sign up to set email alerts
|

Mejoramiento de la producción de nogal pecanero por zinc en riego por goteo en suelos calcáreos

Abstract: El nogal demanda una considerable cantidad de zinc (Zn) para la actividad de enzimas dependientes de Zn que intervienen en el metabolismo de proteínas, azúcares, carbohidratos y auxinas. Por ello, el objetivo de este estudio fue evaluar la producción de nogales con aporte edáfico de 12 a 15 kg ha-1 zinc quelado mediante riego por goteo, además de la adición de un consorcio microbiano comercial en un estudio de tres años. El control fue el manejo convencional de fertilización con zinc foliar. La metodología pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The pH of the calcareous soils where the pecan tree was established was high in all the orchards in this study. Olivas-Tarango et al [21] reported a pH of 7.5 in pecan tree soils in Chihuahua and a high presence of ectomycorrhized roots. In the study by Becerra et al [48], the greatest ectomycorrhizal colonization of Alnus acuminata occurred in soil with a pH of 6.6; in this study, the ECM percentage was measured in soils with pHs ranging from 5.6 to 6.6.…”
Section: Phmentioning
confidence: 99%
See 3 more Smart Citations
“…The pH of the calcareous soils where the pecan tree was established was high in all the orchards in this study. Olivas-Tarango et al [21] reported a pH of 7.5 in pecan tree soils in Chihuahua and a high presence of ectomycorrhized roots. In the study by Becerra et al [48], the greatest ectomycorrhizal colonization of Alnus acuminata occurred in soil with a pH of 6.6; in this study, the ECM percentage was measured in soils with pHs ranging from 5.6 to 6.6.…”
Section: Phmentioning
confidence: 99%
“…In addition, Olivas-Tarango et al [21] reported percentages of ectomycorrhization by Pisolithus sp. of 40 to 70% in a western pecan orchard in Conchos County, Chihuahua, Mexico.…”
Section: Percentage Of Ectomycorrhizal Colonizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Even a large proportion of the applied urea is lost by volatilization, leaching, or by incorporation into the soil ( Avila-Quezada et al, 2022 ). Furthermore, some micronutrients are not available to plants ( Madrid-Delgado et al, 2021 ) mainly in calcareous soil ( Olivas-Tarango et al, 2021 ). For this reason, it is essential to have new nanotechnology-based fertilizers on the market.…”
Section: Eco-friendly Polymer-based Delivery Of Agrochemicals: Minima...mentioning
confidence: 99%